Public debt and inequality in a context of financial openness - Carrera, Jorge Eduardo (2019)
This study analyzes the influence of inequality and financial internationalization on public indebtedness, by controlling for traditional determinants of public debt and using dynamic panel data estimators. The first two factors have shown many changes in the last two decades with a marked heterogeneity between different regions and countries, while the public debt has evidenced a generalized increasing trend. We assume that, in the context of greater access to financial markets, increasing inequality induce governments to issue more debt to offset the negative impact of inequality on the economic growth, the fiscal deficit and financial stability.